(untitled) (Nigerian Journal of Technology, 2021)
A Fused Filament Fabrication (FFF) 3-D printer was fabricated by using in part locally sourced materials. The printer design was based on the Replicating Rapid Prototyper (RepRap) open source. The print volume of the printer is 200mm x 200mm x 300mm and it uses the Melzi V2 printer control board, coupled with the Repetier-Host firmware. The 3-D printer utilizes two major thermoplastic materials namely, the Polylactic Acid (PLA) and the Acrylonitrile Butadiene Styrene (ABS). The printer consists of a frame, fabricated from galvanized steel sheets, stainless steel threaded rods and wooded supports. The three main Cartesian axes of the machine were constructed from plain stainless rods with plastic printed parts as supporting members. Test results obtained for the PLA print material showed a dimensional deviation of 0.307 mm from the actual CAD model at a print temperature of 200°C and at a layer height of 0.2 mm. For the ABS filament, a dimensional deviation of 0.620 mm at a temperature of 255°C, was obtained. Local development and production of this 3-D printer can help in popularizing the benefits of the technology and consequently boosting the local economy.